Blending of supercritical carbon dioxide (SC-CO2) extracted palm kernel oil fractions and palm oil to obtain cocoa butter replacers - Sarker, Md. Zaidul Islam; Nik Ab Rahman, Nik Norulaini; Abd Kadir, Mohd Omar; R. L., Smith Jr. (Elsevier, 2007)
Palm kernel oil (PKO) was fractionated into four fractions using supercritical carbon dioxide (SC-CO2) denoted as f-PKO (f-PKO-1, f-PKO-2, f-PKO-3 and f-PKO-4). The f-PKO-3 and f-PKO-4 were denoted as low lauric (C12) and high oleic (C18:1) constituents which were blended with conventionally extracted palm oil (PO) and fatty acid supplements of commercial C18:0 and commercial C18:1 constituent at different ratios to obtained cocoa butter replacers (CBRs) to define 10 blends. The C12 was reduced to 17.9% and C18:1 was increased to 37.8% in the blends referred to f-PKO-3 as a blend component. Whereas referred to f-PKO-4 as a blend component the C12 was reduced to 14% and C18:1 increased to 38.4%. Although C18 13C14 remain and C18:0 constituent was still lower than that of commercial cocoa butter (CB) in some blends, it did not affect other physico-chemical properties, especially to slip melting point (SMP) and solid fat content (SFC). However, the remaining C12 and C14 of blends 1 1310 could be reduced by further blending with commercial CB or milk fat to use as non-C12 CBRs or could be used as low C12 content CBRs in chocolate product and coating materials. In blend 1 (referred to f-PKO-3 and f-PKO-4 as blend components) where SMP was higher than commercial CB, thus, the SFC value did not drop to 0% at 37.5 C. In referring f-PKO-3 and f-PKO-4 as blend components the SMP and SFC from blends 2 1310 were found to be closer to that of commercial CB. SFC of the blends 2 1310 was found to be higher at 20 C and 0% at 37.5 C. The other properties like iodine value (Iv), saponification value (Spv) and acid value (Av) for the blends 1 1310 were found to be closer to that of commercial CB. From analysis of 10 blends the blending ratios were correlated with multiple linear regression equation and it was found that there was a strong relationship with the fatty acids constituents, SMP, Iv, Spv, Av and SFC. All blends were found to be able to use as CBRs. 2006 Elsevier Ltd. All rights reserved.